The relationship between the incidence of Myopia with the use of gadgets in students of Bersama Private Middle School Berastagi (Talenta Publisher, 2020)
Refractive errors are the failure of the eye to focus light from an object to the retina to form a clear picture. Refractive disorders are divided into myopia, hypermetropia, and astigmatism. Inadequate light, reading books, watching television and using mobile phones for long periods of time are found to be statistically significant risk factors for refractive abnormalities. The purpose of this study is to analyze the correlation between risk factors for refractive abnormalities. This research is an analytic study with cross sectional research design. Research data is primary data obtained through interviews using a research instrument in the form of a questionnaire. The results were obtained from 96 students, there were 33 students with refractive abnormalities with fewer males than females (24% compared to 76%). The results of statistical calculations with the Chi Square correlation test showed no significant correlation between the occurrence of refractive errors with a history of refractive errors in siblings (p = 0.223), and there was a significant correlation between reading activity (p = 0.001), activity using gadgets (p = 0,0001) and outdoor activities (p = 0.041). The conclusion from this study there is no meaningful correlation between the risk factors of history of refractive errors in siblings and there is a significant correlation between the risk factors of reading activity, activities using gadgets and outdoor activities on the occurrence of refractive errors in students of Bersama Private Middle School Berastagi in 2019.